A prospective study to evaluate the safety and efficacy of symbiotic supplementation (probiotic and prebiotic combination) in stage 5D chronic kidney disease patients - Srinivasa, Sanjay; Madhusudhan, Santhosh K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Chronic Kidney Disease (CKD) is one of the major health disorders associated with significant morbidity and mortality. This was a 6 week’s interventional study of orally administered, symbiotic supplement (probiotic with prebiotic) in stage 5D patients of chronic kidney disease (CKD) on twice a week hemodialysis. The objective was to look for safety of symbiotics (Nitrophage ForteTM) and for its anti-inflammatory effects measured by serum hsCRP (Highly specific C reactive protein), IL-6 (Interleukin- 6) and TNF-α (Tumour Necrosis Factor- α) levels. This translating to improvement in the Quality of life (QOL) assessed using SF-36 QOL questionnaire and Subjective Global Assessment (SGA) scoring. Methods: Subjects on twice a week dialysis for at least 3 months were included. Parameters at baseline (representing previous 3 months) were compared to that at the end of treatment. Oral supplementation of strain specific and unique composition of symbiotic sachet supplementation were administered twice daily containing Lactobacillus acidophilus 400mg, Bifidobacterium longumm 400mg, Streptococcus thermophilus with Fructooligosaccharide 100mg adding to 1 gram was given for 6 weeks. Results: 38 patients out of total 48 enrolled completed the study. Symbiotic therapy was found to be well tolerated with no significant adverse effects. 60.52%, 55.26%, 44.7% of the patients had a decrease in hsCRP, TNF-α and IL-6 respectively. Among responders hsCRP and TNF-α showed significant decrease in levels from the baseline (p <0.05). Modified SF-36 QOL questionnaire mean score revealed significant improvement in general health (p < 0.05). Among secondary parameters renal biomarkers like urea, BUN and sodium showed statistically significant decrease (p <0.05). Conclusions: This study establishes the safety and anti-inflammatory efficacy of this symbiotic supplement. To our knowledge this is the first study looking at anti-inflammatory role of symbiotic in CKD 5D Patients. A placebo controlled, double blinded study with a larger sample size is warranted in future to further establish these findings.